Cucut: Estetika Pertunjukan Wayang Kulit Gaya Keraton Lakon Irawan Rabi Sajian Purbo Asmoro - Dimas Winando Pradana Putra; Tatik Harpawati (Lembaga Pengembangan Kinerja Dosen, 2026)
The aesthetics of Palace style puppet performances embody local wisdom and ancestral traditions that were later standardized into formal rules. Purbo Asmoro incorporates these elements of the Palace style into the shadow puppet performance of the play Irawan Rabi. The central problem addressed is: how is the aesthetic concept of cucut implemented in Purbo Asmoro's presentation of the Palace style shadow puppet play Irawan Rabi? This issue is analyzed using the aesthetic concepts proposed by Sunardi, supplemented by those of M.Ng. Najawirangka. The data collection methods included literature reviews and interviews; to ensure higher data accuracy, the play was also transcribed through the observation of audio visual recordings. The results of this study indicate that the implementation of the cucut aesthetic concept is evident in Purbo Asmoro's success in constructing scenes that evoke a humorous impression. This is observable in the ginem of the Dwarawati State audience scene; the ginem of the perang ampyak; the sabet of the perang gagal scene; the ginem of the Yasarata Hermitage scene; the sabet of the perang kembang scene; the ginem of the Kaputren Dwarawati State scene; the ginem of Dwarawati Palace scene; and the ginem of rabine Irawan scene.